2016
DOI: 10.1111/maec.12349
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic distinctness in the diet of two sympatric marine turtle species

Abstract: Marine turtles are considered keystone consumers in tropical coastal 25 ecosystems and their decline through overexploitation has been implicated in the 26 deterioration of reefs and seagrass pastures in the Caribbean. In the present study, 27we analysed stomach contents of green (Chelonia mydas) and hawksbill turtles 28 indicated that green turtles had the most selective diet, whereas hawksbill turtles 45 were less selective than expected when compared with the relative frequency and 46 biomass of diet items.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…In any case, the fast acquisition after settlement in coastal areas of a microbiota adapted to ferment polysaccharides should enable green turtles to adopt an herbivorous diet soon after recruitment. This is the pattern reported from tropical areas [ 25 , 83 ], but in warm temperate and subtropical regions, juvenile green turtles are best described as plant-based omnivore and only adults are primarily herbivores [ 19 21 , 23 , 33 , 34 , 37 , 84 , 85 ]. The results presented here indicate an increase in the taxonomic richness of the gut microbiome as turtles grow, but this is an unlikely explanation by the progressive ontogenetic dietary shift, because even small turtles had a high abundance of Ruminococcaceae and Lachnospiraceae .…”
Section: Discussionmentioning
confidence: 53%
“…In any case, the fast acquisition after settlement in coastal areas of a microbiota adapted to ferment polysaccharides should enable green turtles to adopt an herbivorous diet soon after recruitment. This is the pattern reported from tropical areas [ 25 , 83 ], but in warm temperate and subtropical regions, juvenile green turtles are best described as plant-based omnivore and only adults are primarily herbivores [ 19 21 , 23 , 33 , 34 , 37 , 84 , 85 ]. The results presented here indicate an increase in the taxonomic richness of the gut microbiome as turtles grow, but this is an unlikely explanation by the progressive ontogenetic dietary shift, because even small turtles had a high abundance of Ruminococcaceae and Lachnospiraceae .…”
Section: Discussionmentioning
confidence: 53%
“…species richness) has been a common practice in ecological studies for the past couple of decades (Von Euler & Svensson 2001, Heino et al 2005, Winter et al 2013. But despite its potential application as a measure of diversity in species diets, to our knowledge TD has only been implemented as a measure of diet breadth in 1 recent study involving the diet of turtles (Stringell et al 2016). In the present study, we found that diet TD (represented by the TD among prey families in the diet) was the secondbest predictor of tapeworm species richness in sharks following diet breadth (prey family richness), and similar to general diet breadth, diet TD showed a highly significant positive effect on tapeworm richness when PICs were used to control for confounding of phylogenetic relationships among sharks.…”
Section: Discussionmentioning
confidence: 99%
“…An expanded version of Seagrass dominant. Seagrass contribution to diet is greatest in the following sub-regions: Indian SW (mean = 95.0%; n = 1; Stokes et al 2019), Indian NW (mean = 83.3%; SE = 9.6; n = 4; e.g., Hasbún et al 2000), Indian NE (mean = 65.1%; n = 1; Whiting et al 2014), Pacific SW (mean = 59.3%; SE = 10.4; n = 13; e.g., Fuentes et al 2006;Prior et al 2016), Atlantic NW (mean = 57.5%; SE = 8.2; n = 19; e.g., Mortimer 1981;Stringell et al 2016) and Mediterranean (mean = 46.0%; SE = 19.4; n = 5; e.g., Karaa et al 2012). All studies that recorded no seagrass (or virtually none) in the diet are from regions with limited documented seagrass distribution (e.g., Pacific E and Atlantic SW) ( Fig.…”
Section: Global Review Of Green Turtle Dietmentioning
confidence: 99%
“…In the literature, spatial variation in green turtle diet has often been explained by a combination of environment (e.g., food availability, different habitats) and characteristics of the gastrointestinal microbiome which are influenced by diet (Bjorndal 1997;Price et al 2017). For example, seagrass Thalassia testudinum dominates the Caribbean benthos and is the dominant food item (e.g., Stringell et al 2016); while in the Galapagos (Carrión-Cortez et al 2010) and at Heron Reef Australia (Forbes 1996), the benthos is dominated by macroalgae which comprise most of the diet. Recent advances in knowledge indicate, however, that regardless of diet, the microbiome in green turtles contains the same bacterial phyla although bacterial community composition changes over time in response to diet (Ahasan et al 2017;Campos et al 2018;Bloodgood et al 2020).…”
Section: Gut Microfloramentioning
confidence: 99%